Central Mechanisms of Abnormal Sympathoexcitation in Chronic Heart Failure - Takuya Kishi; Yoshitaka Hirooka (Cardiology Research and Practice)
It has been recognized that the sympathetic nervous system is abnormally activated in chronic heart failure, and leads to further worsening chronic heart failure. In the treatment of chronic heart failure many clinical studies have already suggested that the inhibition of the abnormal sympathetic hyperactivity by beta blockers is beneficial. It has been classically considered that abnormal sympathetic hyperactivity in chronic heart failure is caused by the enhancement of excitatory inputs including changes in peripheral baroreceptor and chemoreceptor reflexes and chemical mediators that control sympathetic outflow. Recently, the abnormalities in the central regulation of sympathetic nerve activity mediated by brain renin angiotensin system-oxidative stress axis and/or proinflammatory cytokines have been focused. Central renin angiotensin system, proinflammatory cytokines, and the interaction between them have been determined as the target of the sympathoinhibitory treatment in experimental animal models with chronic heart failure. In conclusion, we must recognize that chronic heart failure is a syndrome with an abnormal sympathoexcitation, which is caused by the abnormalities in the central regulation of sympathetic nerve activity.